A proposta de ensino por investigação e o processo de formação inicial de professores de ciências: reflexões sobre a construção de um modelo didático pessoal - Gazola, Rodrigo José Cristiano [UNESP] (2013)
In this dissertation, through collaborative research, was intended from the opportunity to connect with a different formative proposal, verify if undergraduates, from a degree course in Chemistry, take a different posture from the conventional, in other words, produces responsibility the subject by building a educational personnel model. Therefore, working with research subjects was constructed collectively, where the individual becomes subject of learning, taking account the inquiry based proposal as articulating principle of experimental and epistemological biased in science education. From this perspective, worked with graduate students in Chemistry in development and implementation of educational activities, which served as main target for the development and analysis. This acting of the researcher sought to integrate new teaching principles in the teaching model of teachers in training, in other words, subsidies so that these subjects could reformulate this model in agreement with an integrated perspective to search results. The analysis of generated material has allowed the perceive that participation in this kind of activity, attracted the attention of prospective teachers for a more dynamic teaching perspective and elaborate than the prospect attended during thei formation. This new perspective led to the teachers in formation the critical view ability about their own formation and showed them ways to reshaping a process of continuous evolution and of their teaching it is also evident that not all licensees, despite having been submitted to the same formative proposal respond the same way to it. Thus, the results of the research suggest that investment in formative proposals that allow the subject in formation initial or continuing opportunities to reflect on their actions is needed in, not only in specific disciplines or specific courses of continuing formation